Pengaruh Substitusi Tepung Sukun Pada Pembuatan Mie Terhadap Sifat Sensoris Dan Kadar Seratnya - galih andika murdaka; Ambar Rukmini; Anggri Sekar Sari (Universitas Widya Mataram, 2025)
Some regions utilize breadfruit as food by boiling, frying, or processing it into cassava. However, breadfruit has the opportunity to be processed into breadfruit flour noodles generally use the basic ingredients of wheat flour. This study aims to determine 1) the effect of breadfruit flour substitution quality on wheat flour in making noodles, 2) The level of liking and public acceptance of the quality of breadfruit noodles, 3) The level of fiber content contained in breadfruit noodles. The sampling technique used a questionnaire with written criteria and breadfruit flour substitution with 16 samples of semi trained panelists and 60 untrained panelists. The level of fiber content used laboratory tests with 3 trials at Chemix-Pratama Laboratory. Breadfruit noodle making was conducted at the Integrated Laboratory of Sarjanawiyata Tamansiswa University and Gatak village, Sumberagung, Jetis, Bantul. The results of this study showed; 1) there was an effect of breadfruit flour substitution on the quality of noodles, 2) the results of the highest public liking test on breadfruit noodles with a percentage of 15%, 3) the results of laboratory tests of the highest fiber content were the percentage of 50% (5.1597gr), then the percentage of 0% (2.8268 gr) the lowest crude fiber content.